Exercise effects on neuropsychiatric symptoms and quality of life in mild cognitive impairment: a systematic review and meta-analysis - Chen, Liang; Kim, Sung Min (Frontiers in Neurology, 2024)
Background Exercise is considered as a cost-efficient option for individuals with mild cognitive impairment (MCI). Although the potential benefits of exercise for improving cognitive function are recognized, its impact on neuropsychiatric symptoms (NPS) and the quality of life (QoL) in individuals with MCI remains unclear. Objective This study aims to investigate the effects of exercise interventions on NPS, including depression, anxiety, sleep disorders, and the quality of life in individuals with MCI. Results There were 17 randomized controlled trials (RCTs) involving 1,575 participants were included. The findings indicate a small but significant positive effect of exercise on depression (standardized mean difference [SMD] = −0.47, 95% confidence interval [CI]: −0.73 to −0.21), but the quality of the evidence is low. Mind–body exercises were relatively more effective in alleviating depression. No significant improvements were observed in sleep disorders (SMD = −1.27, 95% CI: −2.80 to 0.26). Exercise improved anxiety in one study but had no effect in the other. It also improved quality of life in seven studies, with two showing no effect. Conclusion The findings suggest that exercise, particularly mind–body exercises, can improve depression in individuals with MCI. However, the effect of exercise on anxiety, sleep disorders, and quality of life is still uncertain, necessitating additional research. These findings underscore the significance of integrating customized exercise programs in managing MCI to boost quality of life and mitigate NPS. Systematic Review Registration https://www.crd.york.ac.uk/prospero/. ID: CRD42023445369.